Awareness And Legal Protection For Nursing Staff At Dharma Yadnya Hospital, Denpasar - Ni Komang Apriani; I Wayan Budiasa; I Nyoman Bagiastra (CV. AFDIFAL MAJU BERKAH, 2026)
This study aims to analyze the awareness and implementation of legal protection for nursing personnel at Dharma Yadnya General Hospital in Denpasar. The research is motivated by the high legal risks faced by nurses due to unclear boundaries of medical authority and the weak legal protection system within hospital institutions. The study employs an empirical legal method with a qualitative descriptive approach through in-depth interviews with nurses and hospital management, as well as document analysis of relevant regulations and internal policies. The findings reveal that legal protection for nursing personnel at Dharma Yadnya Hospital remains general in nature, lacks a specific legal assistance unit, and has no clear internal guidelines. Legal, structural, and cultural factors significantly influence the effectiveness of legal protection, where the hospital’s adherence to the Tri Hita Karana philosophy often creates a dilemma between maintaining harmony and asserting legal rights. In conclusion, strengthening legal protection for nurses requires the establishment of a legal protection unit, the formulation of internal delegation guidelines, and continuous legal awareness training grounded in professional and spiritual values.